Rehabilitation of the Edentulous Maxilla after the Failure of an Implant-Supported Bar - Yoav Grossmann, DMD, MHA1 and Marianna Pasciuta, DDS, MS2 (Journal of Prosthodontics, 2007)
Dental implants provide patients with multiple restorative options for the complete edentulous maxilla.